(Re)Translokation von St. Petersburg: Dostoevskijs Filmtrip auf Hokkaido, in Livorno, in Paris - Grigor′eva, Nadežda (Wiener Slawistischer Almanach, 2025)
In Dostoevsky’s body of work, the city on the Neva is a place that breaks the text’s link to time and space and transforms every real existing topos into a kind of dystopia. Petersburg itself is translocated, not to some other part of the planet, but quasi beyond the world’s boundaries. The film adaptations of Dostoevsky’s works repeat the translocation of Petersburg and retranslocate the city yet again: most filmmakers shift the location of the action to a completely different cultural and geographical space. In the film adaptations by Akira Kurosawa, Luchino Visconti and Robert Bresson, local, ‘native’ features of the locations collide with the attempt to project transcendent content onto the screen.